Pashto and English Newspaper Discourse Analysis Perspectives Based on Halliday’s Functional Grammar - Abdul Rahim Rahimi (Integrated Journal for Research in Arts and Humanities, 2022)
This investigation compares and contrasts the use of meta-discourse markers in Pashto and English newspaper editorials as persuasive texts. The aforementioned markers are textual components that serve Halliday's (1985) textual and interpersonal objectives while not adding to the propositional substance of the text. Whether metadiscoursal markers were used differently in English and Pashto newspaper editorials was the main research issue. The most prevalent markers from the five subcategories of Text Connectives, Illocution Markers, Hedges, Emphatics, and Attitude Markers were initially found in both English and Pashto newspapers. The frequency of appearance of these markers was then noted in a corpus of 34 editorials (15,000 words each) that were randomly chosen from a variety of English and Pashto newspapers. The significance of the total x2 obs was then demonstrated using a two-way chi square analysis. The null hypothesis of no difference was thus categorically refuted. In order to determine the relative contributions of each subcategory to the overall x 2 value, one-way chi square analysis were employed on the subcategories. Our results showed that only two of the marker subcategories were statistically significant. The many spirits that live in the communities under study are mostly to blame for this discrepancy.